Mechanistic understanding of monoethanolamine (MEA) key role in removal of burnt oil residues - Calabrese, Maria; Schirone, Davide; Mateos, Helena; Valentini, Alessandra; Ditaranto, Nicoletta; Amoroso, Gaia; Speranza, Stefano; Colafemmina, Giuseppe; Palazzo, Gerardo (Colloids and Surfaces A: Physicochemical and Engineering Aspects, 2025)
Ethanolamines are often added in the empirical formulation of commercial hard-surface cleaners and degreasers. Their use is usually justified by the fact they are anti-corrosive agents. However, their direct influence on cleaning performance is not well understood. In this work the cleaning performance of formulations with and without mono-ethanolamine (MEA) have been tested on standard polymerized grease baked on stainless steel plates. We demonstrate, for the first time, that even a small amount of MEA in water is crucial to obtain an efficient removal of burnt residues formed during baking processes. To rationalize this previously overlooked role, we have characterized the soil composition by infrared (IR) and X-ray photoelectron (XPS) spectroscopies and determined its Hansen solubility parameters. In parallel, the effect of MEA aqueous solutions on the soil was investigated by confocal microscopy, contact angle and IR measurements. IR measurements indicate that MEA modifies the baked soil softening it. Confocal imaging demonstrates that the MEA aqueous solution penetrates through the polymerized grease film wetting the substrate and inducing the softened soil retraction from the substrate (deweeeting).
Publisher Copyright: © 2025
Keywords: Degreasing; Detergency; Dewetting; Hard surface cleaners; MEA